THE ROLE OF MUSIC TEXTBOOKS IN CONVEYING THE CULTURAL HERITAGE - Ömer Can SATIR (Fırat University, 2019)
The purpose of this study is to analyze works of Traditional Turkish Music (TTM) origin in primary education music textbooks with respect to “maqam” (a type of melodic mode system), “usûl” (a type of rhythmic cycle), and style and determine to what extend these play role in conveying the cultural heritage. The data set and sample of the research consists of songs and anonym folk songs that are composed/created with a maqam mode and are found in all course levels of primary school teacher guides and student workbooks, which are accepted as educational tools by the Ministry of Education Turkish Education Board. According to this, while there was a clear unbalance in the quantitative distribution of works of TTM origin that were available in primary school music textbooks; in terms of maqams, all the primary education process was based on the “Segâh”, “Hüseyni”, “Uşşak”, “Nihavend”, “Rast”, “Mâhur”, “Gerdâniye”, “Hicaz”, and “Acem Kürdi” maqams. An important finding of the study is that the “Uşşak-Hüseyni” family was, by far, distinctly prominent in these, which proves the deficiency of maqam